BDNF Val66Met polymorphism, energy intake and BMI: a follow-up study in schoolchildren at risk of eating disorders - Aranda Nuria; Ferrer-Barcala Marta; Arija Victoria; Canals Josepa (BMC, 2010)
Abstract Background Eating disorders (ED) have a multifactorial aetiology in which genetics play an important role. Several studies have found an association between the Val66Met (G196A) polymorphism of the Brain-Derived Neurotrophic Factor (BDNF) and Eating disorders. The aim of this study was to determine the association of the Val66Met (G196A) polymorphism of the BDNF gene and its effect on eating disorders (ED), energy intake and BMI in schoolchildren. Methods Two-year cohort study (preadolescence to adolescence). From an initial sample of 1336 Caucasian children (mean age = 11.37 years), a group at risk of ED (n = 141) and a control group (n = 117) were selected using the Children's Eating Attitudes Test. Two years later, they were re-classified into an at-risk group (n = 41) and a control group (n = 159) using the Eating Attitudes Test. The diagnosis of the individuals at risk of ED was confirmed by means of the Diagnostic Interview for Children and Adolescents. BMI, energy intake and the Val66Met (G196A) polymorphism of the BDNF gene were analysed in the at-risk and control groups. Results The frequency of genotypes of the Val66Met (G196A) polymorphism of the BDNF gene is 28.6% (95% CI: 22.4-34.9) in the heterozygous form (Val/Met) and 5% (95% CI: 2.4-9) in the homozygous form (Met/Met). We detected no association between Val66Met genotypes and the severity of ED. Over time, the carriers of the Met66 allele with a persistent risk of ED significantly restricted energy intake (507 Kcal/day; p = 0.033). Conclusion We have not found an association between Val66Met (G196A) polymorphism of the BDNF and ED in schoolchildren from general population. The relationship found between this polymorphism and energy intake restriction in adolescents with a persistent risk of ED should be replicated in a larger sample.